2017
DOI: 10.1038/s41598-017-08244-y
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of complex networks of memristive devices

Abstract: We describe the memristive properties of cluster-assembled gold films. We show that resistive switching is observed in pure metallic nanostructured films at room temperature and atmospheric pressure, in response to applied voltage inputs. In particular, we observe resistance changes up to 400% and archetypal switching events that have remarkable symmetry with the applied voltage. We associated this symmetry with ‘potentiation’ and ‘anti-potentiation’ processes involving the activation of synapses and of pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 47 publications
1
71
0
Order By: Relevance
“…15 Recently, we reported that resistive switching networks can be fabricated by supersonic cluster beam deposition (SCBD) of Au clusters near the percolation threshold. 16 In particular, we have studied the role of substrates in determining the characteristics of the observed switching behavior. 17 Tailoring the conductivity of networks of nanoobjects showing RS is typically achieved by engineering the junctions between the different components and/or by the careful control of the volume fraction of the conducting phase that must be xed close to the electrical percolation threshold.…”
Section: Introductionmentioning
confidence: 99%
“…15 Recently, we reported that resistive switching networks can be fabricated by supersonic cluster beam deposition (SCBD) of Au clusters near the percolation threshold. 16 In particular, we have studied the role of substrates in determining the characteristics of the observed switching behavior. 17 Tailoring the conductivity of networks of nanoobjects showing RS is typically achieved by engineering the junctions between the different components and/or by the careful control of the volume fraction of the conducting phase that must be xed close to the electrical percolation threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Schirm and co-authors [30] used EM to toggle the conductance of an aluminum atomic contact between two well-defined values in the range of a few conductance quanta. More recently, the concept of EM-stimulated resistance switching has been applied to cluster-assembled gold films by Minnai et al [31] and remains a promising approach in current-controlled oxygen doping in YBa 2 Cu 3 O 7−δ [32,33]. Interestingly, the threshold logic implemented by memristive devices permits to emulate synaptic actions in which the memristance of the device can be incrementally modified and a thresholding system governs the firing of the output [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The loss in controllability of synaptic weight at the level of individual memristors is offset by the gain in neuromorphic topology, with the connected network better resembling that of neurobiological systems. [23] Examples of such neuromorphic networks are those formed by atomic switches, [24][25][26][27] nanoparticles, [28][29][30][31][32] or nanowires. [33][34][35] Neuromorphic networks act also as resistive switching devices at the system-level, changing from a high resistance state (HRS) to a low resistance state (LRS) as a result of applying a voltage difference between two terminals across the network.…”
mentioning
confidence: 99%